Steph23465
Steph23465
04-02-2016
Mathematics
contestada
Y=-2x-6
Y=x+9
Elimination method
Respuesta :
apologiabiology
apologiabiology
04-02-2016
so we have
y=-2x-6
y=x+9
elimination
multiply second by e
2y=2x+18
just add them
y=-2x-6
2y=2x+18 +
3y=0x+12
3y=12
divide by 3
y=4
subsitue
4=x+9
subtract 9
-5=x
x=-5
y=4
Answer Link
VER TODAS LAS RESPUESTAS ( 39+ )
Otras preguntas
Which causes athlete’s foot?
How do I convert negative 3 over 5 to a decimal
factor completely if the polynomial is not factorable write prime also state the methods used to factor the polynomial. 1. x^2-12x+36 2. r^3-81r 3. 35x^3y
A bus slams on its breaks and goes from 30 km/hr to 15km/hr in 4 seconds. What is its acceleration?
22.) -5n+3(6+7n) 23.) -2n-(9-10n) 24.) 10-5(9n-9)
Which condition was most necessary for a monarch to gain power? why?
A car is driven 100 kilometers in the 1st week, 130 kilometers in the 2nd week, 160 kilometers in the 3rd week, and so on. What will be the total distance trave
What are the “soils” of democracy?
How do you write 8.59 in word form
Which condition was most necessary for a monarch to gain power? why?